Spectral investigations of low-temperature plasma induced in CO2 gas by nanosecond pulses of extreme ultraviolet (EUV). (5th November 2021) - Bartnik, A; Skrzeczanowski, W; Wachulak, P; Fok, T; Węgrzyński, Ł; Szczurek, M; Fiedorowicz, H
Abstract: In this work, low-temperature plasmas, induced in a gaseous CO2 by intense extreme ultraviolet (EUV) pulses were investigated with a purpose to determine their ionic/molecular composition and the resulting, potentially reactive species. Two laser-produced plasma EUV sources based on a xenon gas puff target were used to irradiate and ionize of the CO2 gas. The sources, driven by Nd:YAG lasers of different parameters, delivered EUV beams created using reflective, focusing collectors. The CO2 -based, low-temperature plasmas induced using both systems, emitted radiation in a wide wavelength range, from vacuum ultraviolet (VUV) to visible light (VIS). The radiation was measured using spectrometers and a streak camera operating in these spectral ranges. In the VUV range, multiple emission lines corresponding to ionic and atomic species together with the CO molecular bands were acquired. Spectra from the UV–VIS range were mainly composed of the CO2 + molecular bands. Numerical simulations of the molecular spectra allowed us to estimate rotational and vibrational temperatures of the EUV induced plasmas. As could be expected, plasmas created in both experimental systems were characterized by different temperatures and intensity ratios of the ionic–atomic spectral lines. The spatio-temporal measurements performed using the streak camera indicated a few times longer lifetime of the EUV induced plasmas, compared to the driving, EUV pulses.